Cultivating political and public identity: Why plumage matters - Barker, Rodney (Manchester University Press, 2017)
"Throughout the twentieth century, everyone from Marxists to economic individualists assumed that social and political activity was driven by the rational pursuit of material gain. Today, the fundamental importance of the cultivation and preservation of identity is finally re-emerging. In this book, Rodney Barker explores the rich fabric of speech, dress, diet and the built environment from which human identity is made. The colour of a scarf or the accent of a conversation can unite people or divide them, and the smallest detail can play its part in signalling who are allies and who are enemies. Identity simultaneously generates equality and inequality - it is both the engine of public life and the cause of its confusion and conflict - and a better understanding of its subtleties is crucial if we are to confront the tensions that it produces in society. Synthesising methods and ideas from numerous disciplines - including history, political science, anthropology, law and sociology - Barker presents a picture of human life as more than just a collection of material interests. His ultimate aim is to show that no human activity is trivial or meaningless, that everything counts and plumage matters."